Prognostic implications of pre-existing medical comorbidity in Takotsubo cardiomyopathy - Nayeri, Arash; Yuen, Alexander; Huang, Cher; Cardoza, Kathryn; Shamsa, Kamran; Ziaeian, Boback; Wells, Quinn S.; Fonarow, Gregg; Horwich, Tamara (Heart and vessels, 2021)
Takotsubo cardiomyopathy (TC) is associated with significant short-term morbidity and mortality. Several risk factors for poor outcomes have been identified; however, the prognostic implications of pre-existing comorbidity in TC are poorly delineated. We sought to assess the association of aggregate pre-existing comorbidity with short-term outcomes in TC. We performed a retrospective observational study of adult subjects diagnosed with TC at two academic tertiary care hospitals between 2005 and 2018. Overall burden of medical comorbidity was estimated using the Charlson comorbidity index (CCI). Multivariable logistic regression was used to test for independent association of CCI with 30-day mortality and severe shock at index presentation. Multivariable poisson regression was performed to assess the association of CCI with duration of hospitalization. Five-hundred and thirty-eight subjects were diagnosed with TC during the study period. The median CCI score of all subjects was 2 (IQR 1–4). Among subjects with physical triggers of TC, the median CCI score was 2 (IQR 1–4) compared to a median CCI score of 1 (IQR 0–1) in subjects with non-physical triggers of TC ( P < 0.001). Seventy-six (14%) subjects died within 30 days of index diagnosis and 185 (34%) subjects experienced severe shock. The median duration of hospitalization was 7 days (IQR 3–14 days). In multivariable logistic regression, CCI was not associated with 30-day mortality or severe shock. In multivariable Poisson regression, CCI (IRR 1.17, 95% CI 1.16–1.18, P < 0.001) was associated with duration of hospitalization. Increased burden of pre-existing medical comorbidity was not independently associated with 30-day mortality or severe shock at index presentation, but was associated with increased duration of hospitalization after diagnosis of TC.